A Helpfulness of Music Therapy on Patients with Chronic Kidney Disease - Nida Roihatul Jannah; Supratman Supratman; Nurlaila Fitriani (Media Keperawatan Indonesia, 2022)
Hemodialysis therapy can cause complications and psychological problems in patients with kidney failure. This problem can do treated with non-pharmacological therapies, one of which is music therapy which can improve health in critically ill patients, and eliminate psychosomatic disorders. This study expects to decide the advantages of music treatment on kidney illness patients going through hemodialysis therapy. The method used is a literature review related to the effectiveness of music treatment on patients with chronic kidney, by searching for the latest relevant literature in the last 5th years through Google Scholar and PubMed. The results of the journal analysis found 12 supporting journals which said that music therapy was effective for reducing physiological (pain, vital signs, and fatigue) and psychological disorders (depression, anxiety, and stress), as well as improving the quality of sleep and quality of life of hemodialysis patients. Music therapy is a relaxation therapy that can do done independently to reduce physiological and psychological problems in hemodialysis patients without having any adverse effects at an affordable cost.